AN EXPERIMENTAL ANALYSIS OF PERCEPTUAL MOTOR APPROACHES TO LEARNING PROBLEMS. (Education)
The purpose of this study was to determine the relative effectiveness of perceptual motor training, and individualized reading instruction on the reading achievement, perceptual motor development, and behavior adjustment of children with reading problems. Forty-four children ranging in age from 7 to 11 who were in the lower half of their age groups in reading were assigned to a 6 month training program in one of three groups: perceptual motor training, individualized reading instruction, and a placebo control group. Analysis of covariance was used to determine differences among the groups and regression procedures were used to select significant predictor variables within and among the groups. The reading group performed above the other two conditions in reading achievement, the perceptual motor group performed below the level of the other two groups on reading achievement and behavior adjustment, and no significant gains in perceptual motor ability were found for any group. Age and initial level of readiness in specific areas were the most significant determinants between and within treatment conditions. Reading variables were dominant predictors of perceptual motor achievement. Readiness and remedial activities involving symbolic and cognitive stimulus elements were viewed as being superior to the currently widely used perceptual motor activities for readiness, corrective, and remedial instruction for children.